HUBUNGAN PENGASUHAN DI TEMPAT PENITIPAN TERHADAP PERKEMBANGAN PSIKOMOTOR, SOSIAL DAN BAHASA PADA ANAK USIA 1-5 TAHUN DI TPA AL IRSYAD TERNATE 2020 - Muhammad Sobri Maulana (JECIES: Journal of Early Childhood Islamic Education Study, 2020)
A child is a valuable expectation of parents. In order to obtain a healthy and smart children and suitable with their growth, children need should be fulfilled either for physical, psychological, social and spiritual needs. Child birth becomes a problem for a working mother so that there are many day care center for children occurred recently that is expected could replace the role of parents temporarily. The aim of this research was to find out how is the relationship of day care center for children with the development of psychomotor, language and social of 1-5 years old children. This was a correlation research that used cross sectional approach. The population was 1-5 years old children that consisted of 21 children who were entrusted in Al Irsyad day care center and the instrument being used was observation sheet and DDST sheet as well as questioner. Data analysis used technique of Spearman’s Rank for observation and child development (DDST). The analysis result showed that the most dominant care was bad care, suitable with the result of observation (referred to DDST) and the dominant child development was normal, and there was a significant relationship for care in the day care center from the aspect of personal social with the development of child personal social, and yet treatment for soft motoric, language and rough motoric did not have relationship with the development of soft motoric, language and rough motoric of children so that it could be concluded that care in the day care center did not have significant relationship with the child development.